Resolving the anxieties of time in Marcel Proust’s in search of lost time : Swann’s way - Lee, Lim Lilian (2015)
On 14’th November 1913, the first volume of Marcel Proust’s seven part novel In Search of Lost Time: Swann’s Way, was published. Proust’s novel was regarded as groundbreaking as he managed to weave time into the plot of his novel like no other author had done before. While most of his Victorian predecessors wrote their novels in a linear, chronological fashion, Proust’s presentation of time was analeptic and proleptic. Flashbacks and flashforwards are common occurrences as Proust taps of the power of memory to navigate through time. The enigmatic quality of time became a source of anxiety to many living in the modern era. Similarly, Proust anguished about time as he acknowledged its inevitable passing. However, in Swann’s Way, Proust explores the narrator’s tenuous relationship with time and eventually overcomes the antagonistic effects of time through the narrator’s exploration of memory. Proust showed his readers how time can be once more subsumed under man’s control through the workings of the mind.